Arqueologia de uma prática científica em Portugal : uma história da fotografia - Nunes, Maria de Fátima (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this essay, photography is regarded as a scientific practice that played an important role in Portugal during the 19th century. The commemorative role of the Academia das Ciências de Lisboa, in 1940, gave rise to several research hypotheses on another history of photography which can be closely linked to the material construction of the State. Thus, we were able to identify two fundamental references in the history of photography as a scientific practice: José Júlio Rodrigues and Secção Fotográfica da Direcção Geral dos Trabalhos Geográficos.